Unusual Coexistence of Giant Cell Tumor and Small Bone Tuberculosis of the Hand - A Case Report - Charach, Gideon; Grosskopf, Itamar; Shteinvil, Ronen; Ehrnwald, Michal; Nochomovitz, Hila; Charach, Lior; Zusmanovich, Lior; Rogowski, Ori; Argov, Ori (Global Journal of Medical and Clinical Case Reports, 2016)
Background: The coexistence of giant cell tumor (GCT) and metacarpal bone tuberculosis (TB) of the hand has never been described before in the English written literature. We report here a first observation. Case presentation: We report the case of a 49-year-old male who presented with severe pain in his left hand following a blunt trauma. A plain X-ray of the metacarpal bones showed a pathological fracture of the 4th metacarpal bone (diaphysis), and computerized tomography and magnetic resonance imaging studies confirmed the diagnosis of destructive (lytic) lesions. biopsy of the metacarpal lesion revealed a GCT, and tissue cultures were positive for mycobacterium tuberculosis (TB). He was treated by a standard 4-drug protocol of isoniazid, rifampicin, pyrazinamide and ethambutol for 2 months and an additional 6 months of isoniazid and rifampicin. He then underwent excision of the metacarpal lesion, and the pathological examination showed a GCT with cultures negative for TB. Conclusions: The correct diagnosis of this unique combination of pathologies (GCT and metacarpal bone TB) depended on a high index of clinical suspicion, referral to mycobacterial laboratory tests, careful histologic examination of tissue samples and especially radiomorphologic findings.